Cavernous Hemangioma in the Orbital Cavity: Case Report - Almeida, José Afonso de; Gellen, Paula Vitória Bido; Hiramatsu, Daniel Martins; Santos, Mariana Araújo dos; Bitencourt, Larissa; Marceliano, Eduardo Fagury Videira; Galhardi, Michelle Paiva Weydt; Marceliano-Alves, Marília F.; Marques, Eduardo Fernandes (European Journal of Dentistry, 2021)
Cavernous hemangiomas are benign malformations of vascular origin, usually well circumscribed and slow to grow. These lesions can be asymptomatic, being discovered unintentionally in imaging exams or symptomatic, indicated mainly by the presence of proptosis, diplopia, and visual disturbances by optic nerve compression. The complementary exams involve computed tomography associated with contrast, color Doppler, magnetic resonance, and angiography. Treatment can be conservative or surgical depending on the case, and the open therapy usually involves lateral, supraorbital, transconjunctival, transantral, pterional, transnasal, and extradural endoscopic orbitotomy. The present study aimed to report a recurrent case of hemangioma in the orbital cavity signaled by ocular proptosis, hyperemia, and ocular pain.The lesion was achieved through the Weber-Ferguson access with zygomatic osteotomy and preservation of the infraorbital nerve. The excision of the lesion was performed, and the previously displaced fragments were fixed with 1.5 mm mini plates. The patient has a chance of progressing with visual impairment due to considerable manipulation of the optic nerve and is being followed up.The reported case showed a successful diagnosis and therapeutic conduct, remaining now in the evolution and follow-up scenario.
Keywords: hemangioma; cavernous; oral pathology